Aksi Cancel Culture Sebagai Reaksi Warganet Dalam Menyeimbangkan Tatanan Sosial (Analisis Wacana Kritis Norman Fairglouch Pada Kasus Gofar Hilman) - Azmi, Rayhan Muhammad; Prasetio, Arie (eProceedings of Management, 2023)
Changes that occur in the social order of society create a new culture that is currently of particular concern, namely cancel culture. One of the cancel culture cases that happened to gofar hilman has become an indication of the need for social order to cancel culture actions. The method used in this study uses the critical discourse analysis method of norman fairglouch by focusing on the "4 steps of social wrong" dimension which is useful for finding solutions to social irregularities that occur in social order. In addition, the method of critical discourse analysis can see the ideology that has been built by the social order with giving ideology or stigma to the victims of the cancel culture. The cancel culture action that happened to gofar hilman was due to the development of an ideology that was deliberately attached to gofar hilman due to the development of his self - image and behavior on social media. In this research, it can be seen that the social order requires a cancel culture action on the form of justice that has been previously believed. It is useful to be able to maintain social norms that have been built for a long time by the social order. In addition, giving a negative stigma to gofar hilman because the social order sees that there are differences in views between gofar hilman and the social order.